The level of managerial functions practiced by the head of household and family economic status in Kerman, Iran - Yadollahi, Mehdi; Paim, Laily; Othman, Mumtazah; Suandi, Turiman; Beygi, Mohsen Darya (Marsland Press, 2011)
Household management is a process of using the required resources to attain the families’ goals through planning and taking the necessary steps to meet these goals. The aim of this article is to determine, the level of managerial functions practiced by the families, and the relationship between the levels of managerial functions practiced and family economic status. Management functions include five dimensions (planning, coordinating, organizing, directing and controlling). Family economic status included three dimensions (income, expenditure, and ownership of physical asset). The instrument used for this study is a questionnaire survey; the researcher selected 390 households, out of a total of 127,892 families in Kerman City. Data collection was through face-to-face interviews to obtain information from the heads of households. The relationship between household expenditure, income, ownership of physical asset, and management functions was investigated using Pearson product-moment correlation coefficients. Findings indicated that elements of management functions have effect on family economic status, but the affected is not considerable, and there is a weak relationship between management functions and family economic status. It may be interesting for future studies to look at the effect of other elements on family economic status.